2001
DOI: 10.1002/1097-0142(20011201)92:11<2927::aid-cncr10109>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of precore mutant hepatitis B virus in chemotherapy-treated patients

Abstract: A kinetic study of free‐radical solution copolymerization of isobutyl methacrylate and lauryl methacrylate in benzene, initiated with 2,2‐azoisobutyronitrile (AIBN) was performed at different monomer feed compositions, at low conversion level. To avoid the complications of copolymerization kinetics, the compositional‐averaged rate constant method was applied to dead‐end polymerization in constant and variable volume polymerization systems. A conditional probability approach, with “maximum likelihood function” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…Moreover, researchers have pointed out that the relapse rate was considerably higher among patients with the pre-core mutant than the ones with non-precore mutant after medical operation [11] . Studies also showed that there was close relationship between HBV pre-core mutation and severe hepatitis in those HCC patients involved in HBV infection during the chemo-therapy [12,13] . Among those patients with severe CHB, studies revealed a mutation rate as high as 88.89%, with a relatively higher content of HBV-DNA in serum [14] .…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, researchers have pointed out that the relapse rate was considerably higher among patients with the pre-core mutant than the ones with non-precore mutant after medical operation [11] . Studies also showed that there was close relationship between HBV pre-core mutation and severe hepatitis in those HCC patients involved in HBV infection during the chemo-therapy [12,13] . Among those patients with severe CHB, studies revealed a mutation rate as high as 88.89%, with a relatively higher content of HBV-DNA in serum [14] .…”
Section: Introductionmentioning
confidence: 95%
“…69,94 A limited number of studies also suggest an increased rate of HBV reactivation and mortality associated with development of lamivudine-resistant YMDD mutations during prophylaxis. 69,95 Among the 10 prospective trials, only three included this end point, with two observing no mutants, and only a single study by Hui et al, reporting development of mutant strains with a rate of 4.9%. 75 However, both subjects were found to have YMDD mutants prior to enrolment in the trial and were excluded; though, each had received lamivudine prior to identification of the YMDD mutants.…”
mentioning
confidence: 99%
“…There are several reports on the elevation of HBV DNA polymerase activity after the discontinuation of immunosuppressive agents or chemotherapy with or without fluminant hepatitis. 10,11 We cannot explain this phenomenon properly; however, this was probably caused by the same mechanisms as in the reported cases. We cannot determine whether our treatment is optimal; however, this patient has been well and free of disease for 80 months after BMT.…”
Section: To the Editormentioning
confidence: 65%